The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1111/j.1610-0387.2010.07355.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis caused by the blue pigment VINAMON® Blue BX FW – a Phthalocyanine Blue in a vinyl glove

Abstract: A 44-year-old metalworker suffered from severe hand eczema in spite of treatment with corticosteroid ointments. He had been using protective cotton gloves with blue PVC anti-slip dots on the finger tips. On clinical examination, the backs of both hands were erythematous and thickened while the finger tips showed vesicles. There was a positive patch test reaction to the blue PVC dots of an unworn cotton glove at 72, 96, 120 hours. To identify the causative chemicals, we carried out further patch tests using ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…Patch test reactions to PVC gloves seem to be relatively common among our patients. The evidence for allergens in PVC is increasing (2–12, 17, 20). In our experience, raw materials or detailed information on the ingredients are difficult to obtain from glove manufacturers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patch test reactions to PVC gloves seem to be relatively common among our patients. The evidence for allergens in PVC is increasing (2–12, 17, 20). In our experience, raw materials or detailed information on the ingredients are difficult to obtain from glove manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their extensive use, contact allergy to PVC gloves has been reported relatively seldom, and, in many cases, the specific allergens have remained unknown. The allergens identified so far in PVC gloves include organic pigments (2, 3), bisphenol A (4, 5), adipic polyester (6), formaldehyde (7), benzisothiazolinone (8, 9), di‐(n‐octyl)‐tin‐bis(2‐ethylhexylmaleate) and/or polyadipic acid propylene glycol (10), and 2‐ethylhexylmaleate (11). Some studies have indicated that contact allergy to PVC gloves might be as common as that to rubber gloves, and problems in obtaining detailed information on the ingredients of PVC gloves may complicate the diagnosis of PVC glove‐allergic patients (12).…”
mentioning
confidence: 99%
“…reported five cases of allergic contact dermatitis caused by TPPi in PVC medical gloves . The other allergens incriminated are biocides, plasticizers, stabilizers, and pigments: benzisothiazolinone , formaldehyde , mono(2‐ethylhexyl) maleate , di‐(n‐octyl)‐tin‐bis(2‐ethylhexylmaleate) and polyadipic acid‐co1,2 propylene glycol , pigments and dyes, a reddish‐copper phthalocyanine‐blue complex , an organic pigment, Irgalite Orange F2G , bisphenol A ( ), and adipic polyester .…”
Section: Discussionmentioning
confidence: 99%
“…Although ACD caused by phthalocyanine has never been reported, contact dermatitis caused by benzyl alcohol as a component of various topical medications and even hearing aid material is well known, but none of them have been reported as a component of pen ink. [6][7][8] Although contact dermatitis caused by crystal violet as a component of staining agents has also been reported, this is not the case when it is used in ink. 9 We believe that our patient had ACD caused by either Prussian blue/crystal violet or eosin present in the blue and red inks, respectively, as patch tests showed positive reactions only to these, and gave negative results with other colours (black and green), which also contained the common solvent.…”
Section: Discussionmentioning
confidence: 99%